Soil heavy metal uptake and distribution in silver birch plantations on former agricultural land - Marju Kaivapalu-Kaasik; Katri Ots; Reimo Lutter; Arvo Tullus; Tea Tullus; Reeno Sopp; Hardi Tullus (Environmental Monitoring and Assessment, 2026)

Soil nutrients and organic carbon changes in 20-year repeated soil monitoring in hybrid aspen plantations on former agricultural lands - Natalia Vysotska; Reimo Lutter; Arvo Tullus; Tea Tullus; Reeno Sopp; Alar Astover; Hardi Tullus (Forest Ecology and Management, 2026)

Evaluating Hybrid Aspen Plantations for Phytoremediation of Heavy Metals on Former Agricultural Soils - Marju Kaivapalu-Kaasik; Katri Ots; Reimo Lutter; Arvo Tullus; Tea Tullus; Reeno Sopp; Hardi Tullus (Water, Air, & Soil Pollution, 2026)

Do silver birch (Betula pendula) and hybrid aspen (Populus tremula × P. tremuloides) plantations on former agricultural land differ from the perspective of biodiversity? - Tea Tullus; Reimo Lutter; Tiina Randlane; Andres Saag; Arvo Tullus; Elisabeth Rähn; Taavi Riit; Reeno Sopp; Mari-Liis Siller; Kristjan Täll; Katri Ots; Marju Kaivapalu; et al. (New Forests, 2025)

Ecosystem carbon storage two decades after afforestation in Norway spruce and silver birch monocultures and mixtures on abandoned agricultural land in hemiboreal Estonia - Kristjan Täll; Arvo Tullus; Tea Tullus; Hardi Tullus; Reimo Lutter (Forest Ecology and Management, 2025)

Temporal dynamics of forest understory on former agricultural land follows similar pathways in plantations and naturally regenerated stands - Tea Tullus; Reimo Lutter; Arvo Tullus; Reeno Sopp; Mari-Liis Siller; Aivo Vares; Hardi Tullus (New Forests, 2024)

Ecosystem Carbon and Nutrient Balances in Short-Rotation Hybrid Aspen Coppice Under Different Thinning Methods - Reimo Lutter; Heiki Hepner; Arvo Tullus; Hyungwoo Lim; Tea Tullus; Eele Õunapuu-Pikas; Reeno Sopp; Marju Kaivapalu; Kristjan Täll; Katri Ots; Hardi Tullus (BioEnergy Research, 2024)
Coppice plantations have gained a high interest for biofuel production and carbon uptake in short rotation cycles. There is a limited knowledge how such intensive coppice management affects soil fertility and nutrients supply to maintain carbon sink. We studied ecosystem carbon and nutrients balance and allocation during a 5-year period in hybrid aspen coppice under different thinning methods in hemiboreal Estonia. The benchmark value for the changes was defined before the coppice emerged after the clear-cut of the previously planted hybrid aspen plantation. The studied systematical thinning treatments were as follows: corridor thinning with removal of 67% of the trees (CT), cross-corridor thinning with removal of 89% of the trees (CCT), and unthinned (UT) coppice. The UT and CT treatments resulted in a positive carbon balance at the ecosystem level. In all treatments, a decrease of soil acidity, organic C, total N, K, Mg and Mn contents, and an increase of soil Cu and B contents were observed in the 0–20-cm deep layer. The concentrations of leaf N, P, and K were higher in UT than in the two thinning treatments, indicating that the aspens had not entirely recovered from the changed root to shoot ratio 2 years after thinning, whereas the leaf mass fraction of medium- and small-sized trees had already increased. Bioenergy harvest from the UT site in a 5-year rotation would cause 5–18% removal of NPK from the total ecosystem pool. Overall, hybrid aspen coppice showed positive ecosystem carbon balance after the first 5-year period; however, further monitoring of soil properties is needed as we found decrease of soil organic C and nutrients concentrations in short term. Graphical Abstract

Phytoremediation capacity of hybrid aspen at sites affected by industry and agriculture - Marju Kaivapalu; Katri Ots; Reimo Lutter; Arvo Tullus; Tea Tullus; Reeno Sopp; Heiki Hepner; Mari-Liis Siller; Maris Hordo; Eele Õunapuu-Pikas; Kristjan Täll; Aivo Vares; et al. (Environmental Monitoring and Assessment, 2024)

Rapid shift of soil fungal community compositions after clear-cutting in hemiboreal coniferous forests - Elisabeth Rähn; Leho Tedersoo; Kalev Adamson; Tiia Drenkhan; Ivar Sibul; Reimo Lutter; Sten Anslan; Karin Pritsch; Rein Drenkhan (Forest Ecology and Management, 2023)

Soil fungal diversity of birch plantations on former agricultural land resembles naturally regenerated birch stands on agricultural and forest land - Reimo Lutter; Taavi Riit; Ahto Agan; Elisabeth Rähn; Arvo Tullus; Reeno Sopp; Katri Ots; Marju Kaivapalu; Kristjan Täll; Tea Tullus; Leho Tedersoo; Rein Drenkhan; et al. (Forest Ecology and Management, 2023)

A simulation model of functional habitat connectivity demonstrates the importance of species establishment in older forests - Madli Jõks; Aveliina Helm; Liis Kasari-Toussaint; Ene Kook; Reimo Lutter; Norbertas Noreika; Ede Oja; Maarja Öpik; Tiina Randlane; Ülle Reier; Kersti Riibak; Andres Saag; et al. (Ecological Modelling, 2023)

Effects of air humidity and soil moisture on secondary metabolites in the leaves and roots of Betula pendula of different competitive status - Bikash Kharel; Linda Rusalepp; Biplabi Bhattarai; Ants Kaasik; Priit Kupper; Reimo Lutter; Pille Mänd; Gristin Rohula-Okunev; Katrin Rosenvald; Arvo Tullus (Oecologia, 2023)

Twenty years of afforestation of former agricultural lands with silver birch plantations affects vertical distribution of SOC and macronutrients in the topsoil layer - Reimo Lutter; Arvo Tullus; Aivo Vares; Reeno Sopp; Tea Tullus; Marju Kaivapalu; Katri Ots; Bikash Kharel; Tomas Lundmark; Hardi Tullus (Plant and Soil, 2023)

Effect of Early Thinning Treatments on Above-Ground Growth, Biomass Production, Leaf Area Index and Leaf Growth Efficiency in a Hybrid Aspen Coppice Stand - Heiki Hepner; Reimo Lutter; Arvo Tullus; Arno Kanal; Tea Tullus; Hardi Tullus (BioEnergy Research, 2020)

First record of Entoleuca mammata in hybrid aspen plantations in hemiboreal Estonia and stand–environmental factors affecting its prevalence - Reimo Lutter; Rein Drenkhan; Arvo Tullus; Katrin Jürimaa; Tea Tullus; Hardi Tullus (European Journal of Forest Research, 2019)

Ecosystem carbon stocks of Estonian premature and mature managed forests: effects of site conditions and overstorey tree species - Reimo Lutter; Raimo Kõlli; Arvo Tullus; Hardi Tullus (European Journal of Forest Research, 2019)

Growth development and plant–soil relations in midterm silver birch (Betula pendula Roth) plantations on previous agricultural lands in hemiboreal Estonia - Reimo Lutter; Arvo Tullus; Arno Kanal; Tea Tullus; Aivo Vares; Hardi Tullus (European Journal of Forest Research, 2015)

Understorey vegetation in young naturally regenerated and planted birch (Betula spp.) stands on abandoned agricultural land - Tea Tullus; Arvo Tullus; Elle Roosaluste; Ants Kaasik; Reimo Lutter; Hardi Tullus (New Forests, 2013)